2017
DOI: 10.5812/ijhrba.63196
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subliminal Activation of Abandonment Schema on the Eating Behavior of Obese and Normal Weight Women: An Experimental Study

Abstract: Background: Schema focused cognitive-behavioral model proposed that patients with eating disorders (EDs) used bulimic behaviors in order to avoid or suppress negative affects that are triggered by early maladaptive schemas. Objectives: The aim of the present study was to compare normal weight and obese women in terms of the effect of the activation of abandonment schema. Patients and Methods: This was a 2-stage approach experimental study. In the first, 81 women (41 normal weight and 40 obese) completed the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, the influence of the abandonment schema on depressive symptomatology in women with GD is noteworthy and may be revealing the influence of a relational aspect in women. In fact, in previous studies, abandonment has been related to fear of loneliness, which has been identified as a high-risk factor in female gamblers (Estévez et al, 2021 ; Mohammadkhani et al, 2017 ; Ozawa-de Silva & Parsons, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of the abandonment schema on depressive symptomatology in women with GD is noteworthy and may be revealing the influence of a relational aspect in women. In fact, in previous studies, abandonment has been related to fear of loneliness, which has been identified as a high-risk factor in female gamblers (Estévez et al, 2021 ; Mohammadkhani et al, 2017 ; Ozawa-de Silva & Parsons, 2020 ).…”
Section: Discussionmentioning
confidence: 99%